Preliminary Study of College Students’ Creative Thinking Skills on Electromagnetic Material - Ericha Ayusepta Marviyani; Sukarmin Sukarmin; I Gusti Made Sanjaya (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to analyze the initial ability of student's creative thinking skills on electromagnetic materials and find a solution method of learning model suitable to the students' conditions. Method: The design of this study was pre-experimental. The data collection technique used a test method using creative thinking skills test instrument. The test instruments used in this study were tested for validity and reliability before use. Results: The results of this study showed different results. The percentage of the fluency indicator is 96.71% in the very good category, the percentage of the flexibility indicator is 51.97% in the medium category, the percentage of the elaboration indicator is 36.18%, and the originality is 16.45% in the less category. The average of all indicators is 50.32%, with the medium category. Novelty: Students' creative thinking skills can be developed through various methods, including the PjBL model, the Inquiry Social Learning model, PBL combined with Flashcard media, and PjBL integrated with STEM-based e-learning. The implications of this study can be used as a reference and essential alternative for future researchers to design learning tools using specific learning methods/models to increase students' or college students' creative thinking skills.